Interprofessional socialization as a way to introduce collaborative competencies to first-year health science students. Issue 6 (November 2014) - DiVall, Margarita V; Kolbig, Leslie; Carney, Mary; Kirwin, Jennifer; Letzeiser, Christine; Mohammed, Shan
Abstract Interprofessional education (IPE) is the cornerstone of preparing future health care providers but remains to be a challenge for many health science programs. We aimed to develop and evaluate an interprofessional conference for first-year health science students with goals to provide students with interprofessional socialization opportunity and introduce IPE principles. A half-day conference was based upon core competencies for health professionals and involved 277 first-year health sciences, nursing, pharmacy, physical therapy, and speech language pathology and audiology students. Alcohol and substance misuse was chosen as a topic for its relevance to college students and health professionals. Results from program evaluation revealed that the conference was successful in exposing students to core interprofessional competencies and provided useful information about alcohol and substance misuse. This study advocates for early inclusion of IPE in the health professions curricula in the form of interprofessional socialization.